Mino-bimaadiziwin: ReIndigenizing through Land-based Learning - Henderson, Lindy P (Scholarship@Western, 2024)
In response to the Truth and Reconciliationâ€™s 62nd and 63rd Calls to Action, the author takes a servant leadership approach to embedding Indigenous knowledge to the K-12 classrooms in Ontario with a focus on reIndigenizing through land-based learning. Student well-being and achievement data show Indigenous students in both provincial and Indigenous community schools are below that of their non-Indigenous peers, and the impact of residential schools continues in Treaty 3 territory is an intergenerational crisis that demands immediate attention and shift for educational leadership. As a MÃ©tis scholarly practitioner, the author centres Indigenous research and personal positionality in creating a change implementation plan which focuses on learning from, on, and with the land as a daily act of reconciliation. The traditional medicine wheel is used throughout the Dissertation-in-Practice to align holistic, lifelong learning with change leadership, monitoring, evaluation, and disrupting the status quo. Culturally responsive pedagogy is explored through research and practical examples of shifting practice, policy, and ontological perspectives to outline practical solutions for complex issues. The work is centred on mino-bimaadiizin, the Anishinaabek teaching of leading a good life.